Differential Motor Facilitation During Action Observation in Followers and Leaders on Instagram - Farwaha, Sumeet; Obhi, Sukhvinder S. (Frontiers in Human Neuroscience, 2019)
High power and high socioeconomic status individuals have been found to exhibit less motor system activity during observation of another individual’s behaviour. In the modern world, the use of online social networks for social interaction is increasing, and these social networks afford new forms of social status hierarchy. An important question is whether social status in an online setting affects social information processing in a way that resembles the known effects of real-world status on such processing. Using transcranial magnetic stimulation (TMS), we examined differences in motor cortical output during action observation between Instagram ‘leaders’ and ‘followers’. Instagram Leaders were defined as individuals who have more followers than they are following, while Instagram Followers were defined as individuals who have fewer followers than they follow. We found that Followers exhibited increased Motor-evoked Potential (MEP) facilitation during action observation compared to Leaders. Correlational analyses also revealed a positive association between an individual’s Instagram follower/following ratio and their perceived sense of online status. Overall, the findings of this study provide some evidence in favour of the idea that our online sense of status and offline sense of status might be concordant in terms of their effect on motor cortical output during action observation.